Co-hydroprocessing gas-oil with residual lipids: effect of residence time and H2/Oil ratio. (10th September 2016) - Dimitriadis, Athanasios; Bezergianni, Stella
Abstract: Co-hydroprocessing of petroleum fractions with residual lipids is a promising technology for hybrid fuels production. The aim of this study is the identification of an effective operating window for co-hydroprocessing of Heavy Atmospheric Gas Oil (HAGO) with Waste Cooking Oil (WCO) within the nominal operating limits of a refinery. In particular, two Liquid Hourly Space Velocities or LHSVs (0.66 and 1 h −1 ) and three hydrogen-to-oil or H2 /Oil ratios (300, 400 and 500 L H2 /L feed) were studied for a HAGO/WCO 90/10 V/V blended feedstock over a commercial hydrotreating NiMo/Al2 O3 catalyst. The two parameters were evaluated with respect to the attained diesel content and quality of the produced hybrid fuels. All experiments were performed at a constant pressure of 5.6 MPa and temperature of 350 °C. The results have shown that higher LHSV is preferable in terms of the hydrogen consumption affecting the conversion cost. As far as H2 /Oil is concerned, high H2 /Oil ratios are more effective, rendering higher conversion, diesel content and heteroatom removal. Highlights: Hybrid diesel can be produced via residual lipids co-processing in refinery. High residence time favors lipids co-processing with petroleum fractions. Co-processing requires high H2 /Oil, favoring saturation and heteroatom removal.